Information Support of the Military Service Staff of the Armed Forces of Russian Federation - Stovbur A.P.; Kovrizhin D.B.; Krutoy A.N. (Физическая культура. Спорт. Туризм. Двигательная рекреация, 2019)
Questions of information support of physical training of members of the Armed Forces of Russian Federation. It is demonstrated that there is a need for transformation of information support of physical training in conditions of informatization of society. The paper reflects the terms of main laws of Russian Federation in the field information support of physical training and sport. The elements of the system of information support are described. The paper contains a short description of questions related to the information support within the context of implementation of the Concept of the development of physical training and sport in the Armed Forces of Russian Federation till 2020. The activity of officials responsible for information support of physical training of military service staff was analyzed. The importance of the analysis of problems of information support of physical training military service staff is based, first, on the need to ensure the maximum efficiency of the processes of physical training, and second, on the need to ensure the correspondence between the processes of physical training to the increased level of informatization of the society in general. The goal of the paper is to identify the most prospective ways of optimizations of information support of the physical training of military service staff. The paper is based on the general method of analysis and synthesis. The information basis of the research consists of legal acts regulating the information support of physical training and sport in Russian and more specifically in the Armed Forces of Russian Federation. It is demonstrated that the system of information support of the physical training of the military service staff covers all levels of the Armed Forces of Russian Federation. However, it is necessary to improve this system in order to carry out all tasks included in the Concept of the development of physical training and sport in the Armed Forces of Russian Federation. It is recommended to modify curricula of the military educational institutions, to form a common information space of the support of physical training and to strengthen ties of physical training with other courses in military educational institutions.